Occurrence and activity of cardamom pests and honeybees as affected by pest management and climate change - M.B.2, Ravi R.3, Subbiah A.4, *Murugan M.1, Shetty P.K.1, Hiremath (International Multidisciplinary Research Journal, 2011)
It has been conjectured that global warming will increase the prevalence of insect pests in most agroecosystems. The variability and possible trends in the occurrence and management of cardamom pests climatic variables and productivity were analyzed for cardamom agroforestry system. Analysis showed a general trend of decreasing temperature for temperature maximum since 2000. Year to year variation was noticeable for all parameters analyzed including relative humidity and soil temperatures (15 cm top soil layer) during 2000-2007. Contrary to the general agreement that recent warming had increased the prevalence of insect pests in majority of the agroecosystems, our results showed decreasing incidence of insect pests in cardamom agroforestry system because of calendar-based pesticide spraying. A decrease in natural enemy populations was observed. There has been an increase in number of pesticide sprays by at least one with the passage of each year. The reason for increased rounds of pesticides could be assigned to more prevalence and altered population dynamics of thrips and capsule borers during the study period. This situation has led to higher use of pesticides in cardamom agroecosystem.Ã‚Â